HUBUNGAN ANTARA EFIKASI DIRI DAN KONSEP DIRI AKADEMIK DENGAN PRESTASI BELAJAR MAHASISWA FKIP UNBARI - Yurni Yurni (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
This study was aimed to found out the relationship between academic self efficacy and academic self concept with learning achievement of English department students at Batanghari University Jambi. The academic self concept and academic self efficacy scale was used to know students academic self concept and academic self efficacy. Cumulative index of student achievement was used to know students learning achievement in learning English. There were 47 subjects of this research. The result showed that there were significant relation between academic self concept and academic self efficacy to student learning achievement rxy=0.490 and p=0.000 (p<0.05). The positive value indicated that there were positive correlation between variables.Keyword :  self-efficacy, self-concept, academic achievement